DA5-CH and Semaglutide Protect against Neurodegeneration and Reduce α-Synuclein Levels in the 6-OHDA Parkinson’s Disease Rat Model - Lingyu Zhang; Chun Li; Zijuan Zhang; Zhenqiang Zhang; Qian-Qian Jin; Lin Li; Christian Hölscher (Parkinson's Disease)
Insulin desensitization has been observed in the brains of patients with Parkinson’s disease (PD), which is a progressive neurodegenerative disorder for which there is no cure. Semaglutide is a novel long-actingglucagon-likepeptide-1 (GLP-1) receptor agonist that is on the market as a treatment for type 2 diabetes. It is in a phase II clinical trial in patients with PD. Two previous phase II trials in PD patients showed good effects with the older GLP-1 receptor agonists, exendin-4 and liraglutide. We have developed a dual GLP-1/GIP receptor agonist (DA5-CH) that can cross the blood-brain barrier (BBB) at a higher rate than semaglutide. We tested semaglutide and DA5-CH in the 6-OHDA-lesion rat model of PD. Treatment was semaglutide or DA5-CH (25 nmol/kg, i.p.) daily for 30 days postlesion. Both drugs reduced the apomorphine-induced rotational behavior and alleviated dopamine depletion and the inflammation response in the lesioned striatum as shown in reduced IL-1β and TNF-α levels, with DA5-CH being more effective. In addition, both drugs protected dopaminergic neurons and increased TH expression in the substantia nigra. Furthermore, the level of monomer and aggregated α-synuclein was reduced by the drugs, and insulin resistance as shown in reduced pIRS-1ser312 phosphorylation was also attenuated after drug treatment, with DA5-CH being more effective. Therefore, while semaglutide showed good effects in this PD model, DA5-CH was superior and may be a better therapeutic drug for neurodegenerative disorders such as PD than GLP-1 receptor agonists that do not easily cross the BBB.